Association of anti-Ro/SSA antibody with response to biologics in patients with rheumatoid arthritis. Issue 6 (1st November 2016) - Hagiwara, Shinya; Tsuboi, Hiroto; Honda, Fumika; Takahashi, Hidenori; Kurata, Izumi; Ohyama, Ayako; Yagishita, Mizuki; Abe, Saori; Kurashima, Yuko; Kaneko, Syunta; Kawaguchi, Hoshimi; Takahashi, Hiroyuki; et al.
Abstract: Objective : To compare the effectiveness of three different biologics in anti-Ro/SSA antibody-positive and antibody-negative patients with rheumatoid arthritis (RA). Methods : The study subjects were 110 biologics naïve patients with RA who started treatment with biologics and examined for anti-Ro/SSA antibody between December 2003 and March 2014. For patients treated with intravenous infliximab (IFX), tocilizumab (TCZ), or abatacept (ABT), we compared the clinical characteristics and changes in composite disease activity index, such as DAS28, SDAI, and CDAI, for 12 months in anti-Ro/SSA antibody-positive and antibody-negative patients. Results : We examined 59 patients (nine were positive and 50 were negative for anti-Ro/SSA antibody) treated with IFX, 27 patients (5 positive and 22 negative) treated with TCZ, and 24 patients (13 positive and 11 negative) treated with ABT. For patients treated with IFX, parameters of disease activity did not change significantly from baseline in anti-Ro/SSA antibody-positive patients, whereas they improved in antibody-negative patients. On the other hand, treatment with TCZ and ABT significantly decreased disease activity, relative to baseline, in both anti-Ro/SSA antibody-positive and antibody-negative patients. Anti-Ro/SSA antibody-positive patients treated with IFX showed higher frequency of HACA and seroconversion of ANA, and lower serum TGF-β levels. Conclusions : Positivity to anti-Ro/SSA in RA seems to confer resistance to IFX via production of HACA and ANA, and low serum TGF-β levels, but not to TCZ and ABT.